Rhetoric in competition architecture: a case study of user centrality, organisation of space and context in open architectural contests - Kirilova, Nadia (2016)
In this study I aim to unveil the changes in competition architecture by examining the new trends within the rhetoric of competition submissions to reveal how the user is represented in open competition architecture texts. I also aim to reveal that although symbolic appearances are still an important aspect in the manuscripts, there seem to be a number of relatively new priorities taken into consideration such as openness, flexibility and transparency. Last but not least, special attention is paid to the removal of power effects in design of visual appearances, form and through organisation of space.